Larrie D. Ferreiro. Ships and science. The birth of naval architecture in the scientific revolution, 1600-1800. Cambridge, MIT Press, 2006, 441 páginas. - Garrido, Santiago (2007)
Fil: Garrido, Santiago. Universidad Nacional de Quilmes. Instituto de Estudios Sociales de la Ciencia y la Tecnología; Argentina.